2008
DOI: 10.1126/science.1164446
|View full text |Cite
|
Sign up to set email alerts
|

Carbonatite Melts and Electrical Conductivity in the Asthenosphere

Abstract: Electrically conductive regions in Earth's mantle have been interpreted to reflect the presence of either silicate melt or water dissolved in olivine. On the basis of laboratory measurements, we show that molten carbonates have electrical conductivities that are three orders of magnitude higher than those of molten silicate and five orders of magnitude higher than those of hydrated olivine. High conductivities in the asthenosphere probably indicate the presence of small amounts of carbonate melt in peridotite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
243
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(263 citation statements)
references
References 34 publications
14
243
3
3
Order By: Relevance
“…On the other hand, the high melt ascent velocity may simply be achieved with liquid of much lower viscosity than that of basalt melt, such as carbonaterich melt. Faul 46 argued for the possibility of volatile-rich melts at the deeper part of the mid-ocean ridge to explain high melt ascent rate at low porosities, and recent experimental 10 and electrical conductivity 12,53 results suggest the existence of a small amount of carbonate-rich melt in the asthenosphere beneath the midocean ridge. In addition, a geochemical study by Dasgupta et al 54 suggested that the 230 Th and 231 Pa excesses observed in erupted mid-ocean ridge basalt are a consequence of contributions of carbonate-rich melt.…”
Section: Article Nature Communications | Doi: 101038/ncomms6091mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the high melt ascent velocity may simply be achieved with liquid of much lower viscosity than that of basalt melt, such as carbonaterich melt. Faul 46 argued for the possibility of volatile-rich melts at the deeper part of the mid-ocean ridge to explain high melt ascent rate at low porosities, and recent experimental 10 and electrical conductivity 12,53 results suggest the existence of a small amount of carbonate-rich melt in the asthenosphere beneath the midocean ridge. In addition, a geochemical study by Dasgupta et al 54 suggested that the 230 Th and 231 Pa excesses observed in erupted mid-ocean ridge basalt are a consequence of contributions of carbonate-rich melt.…”
Section: Article Nature Communications | Doi: 101038/ncomms6091mentioning
confidence: 99%
“…Kimberlite magma is characterized by low silica with high magnesium and a C-O-H volatile-rich composition [5][6][7][8] , and is thought to be formed in the presence of H 2 O and CO 2 under conditions close to the carbonate-peridotite solidus in the Earth's mantle [9][10][11] . Small amounts of carbonate-rich melt may also be present in the asthenosphere beneath mid-ocean ridges, according to recent electrical conductivity studies 12,13 and high-pressure and hightemperature experiments 10,[14][15][16] . In addition, strongly carbonated silicate melt is thought to be partly responsible for the presence of oceanic low-velocity zones 10,17 .…”
mentioning
confidence: 99%
“…Aside from the chemical composition, other available alternative causes for high conductivity anomalies can be considered, such as water in nominally anhydrous minerals (Wang et al, 2006;Yang, 2011;Karato, 2009, 2014a), interconnected saline (or aqueous) fluids (Hashim et al, 2013;Shimojuku et al, 2014;Sinmyo and Keppler, 2017;Guo et al, 2015;Li et al, 2018), partial melting (Wei et al, 2001;Maumus et al, 2005;Gaillard et al, 2008;Ferri et al, 2013;Laumonier et al, 2015Laumonier et al, , 2017Ghosh and Karki, 2017), interconnected secondary high conductivity phases (e.g., FeS, Fe 3 O 4 ; Jones et al, 2005;Bagdassarov et al, 2009;Padilha et al, 2015), dehydration of hydrous minerals (Wang et al, 2012(Wang et al, , 2017Manthilake et al, 2015Manthilake et al, , 2016Hu et al, 2017;Sun et al, 2017a, b;Chen et al, 2018) and graphite films on mineral grain boundaries (Freund, 2003;Pous et al, 2004;Chen et al, 2017). In consideration of the similar formation conduction and geotectonic environments, the Himalaya-Tibetan orogenic system was compared with the Dabie-Sulu UHPM belt and explained high electrical conductivity anomalies.…”
Section: Geophysical Implicationsmentioning
confidence: 99%
“…It is difficult to reconcile rapid emplacement of crystal-rich lavas with an estimated viscosity that are five to six orders of magnitude higher than ever measured in the field and/or in laboratory experiments (Dawson et al 1995b;Pinkerton et al 1995;Norton and Pinkerton 1997). However, the extremely low melt viscosities and high diffusion rates that characterize natrocarbonatitic magmas (Gaillard et al 2008) could favor rapid crystallization during emplacement of lava flows (e.g., the crystal content of a solidified lava flow is not identical to the crystal content during emplacement). Previous experimental studies focused on the crystallization of natrocarbonatitic magmas have been conducted at 100 and 20 MPa confining pressure (Cooper et al 1975;Petibon et al 1998).…”
Section: Introductionmentioning
confidence: 93%